2022
DOI: 10.1680/jensu.20.00048
|View full text |Cite
|
Sign up to set email alerts
|

Eco-efficient cementitious composites with large amounts of waste glass and plastic

Abstract: This paper presents an experimental study, which has been lacking to date, into the properties and applications of waste glass–plastic cementitious (WGPC) composites incorporating recycled aggregates as a full replacement of natural aggregates, with direct application in highly eco-efficient construction components. Detailed experimental assessments of the fresh properties, strength and durability characteristics of such composites are undertaken. Particular focus is given to the mix rationale and optimisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The Waste Glass (WG) used in this study comes from mixed cullet of recycled glass bottles (Corbu et al, 2021). A small proportion of WG Powder (WGP) with particle size below 25 microns, resulted from grinding, was studied by means of XRD and the composition results are presented in Table 1 (Corbu et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The Waste Glass (WG) used in this study comes from mixed cullet of recycled glass bottles (Corbu et al, 2021). A small proportion of WG Powder (WGP) with particle size below 25 microns, resulted from grinding, was studied by means of XRD and the composition results are presented in Table 1 (Corbu et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…However, domestic and international studies have reported that there is a critical value of fly ash content, and exceeding this value will destroy the microaggregate effect of concrete. Zhao et al 10 studied the effects of fly ash admixtures and found that the amount of fly ash affects the combination of fly ash and concrete interfaces at the microscale, thus affecting the creep of concrete. The author speculates that under an excessively high admixture amount, there is more free fly ash in the matrix, which prevents full combination at the interfaces and has a negative impact on the concrete (Figure 7(a)).…”
Section: Application Of Industrial Waste Residuesmentioning
confidence: 99%
“…As the academician Sun Wei found, the interface combination of admixtures and cement-based materials is an important factor affecting the performance of cement-based materials. 10,96,97 Therefore, a future research direction is to improve the bonding state of the concrete interface and provide a more direct scientific basis by observing the microstructure and its mechanism. (2) Among the research on the types and dosages of external admixtures in compound admixture technology, there is a lack of studies on the coupled effects of multiple factors, such as the type of external admixture, dosage, water-binder ratio, and curing time.…”
Section: Industrial Waste Residuesmentioning
confidence: 99%
“…Mohammadinia et al [21] showed the feasibility of substituting up to 50% of natural aggregates for a combination of recycled plastic and glass aggregates in the construction of concrete footpaths. Corbu et al [22] found that a combination of recycled aggregates from waste plastic and waste glass can totally replace natural aggregates in precast concrete pieces. Thorneycroft et al [23] proved the feasibility of substituting up to 10% by volume of sand for recycled plastics in the manufacture of concrete.…”
Section: Introductionmentioning
confidence: 99%